miR-28 modulates exhaustive differentiation of T cells through silencing programmed cell death-1 and regulating cytokine secretion - Li, Qing (Oncotarget, 2016)
T cell exhaustion is a state of T cell dysfunction that arises during many cancer. miRNAs are one of major gene regulators which result in translational inhibition and/or mRNA degradation. We hypothesized that miRNAs exist that can silence PD1 and act as a modulator in vitro to revert exhaustive status of T cells. We demonstrated that the exhausted T cells with inhibitory receptors (IRs) are significantly increased in the melanoma-bearing mice. Meanwhile, the differentiated miRNA profiles in PD1+ exhaustive T cells were identified using a miRNA array; 11 miRNAs were observed with significant altered levels in the exhausted T cells isolated from melanoma-bearing mice. Among those identified miRNA candidates, miR-28 was capable of binding to multiple IRs based on an in silico analysis and subsequently silencing PD1, as demonstrated by a dual luciferase assay. Moreover, the expression of PD1 was attenuated after transfection with miR-28 mimic. The ability of miR-28 in regulating T cell exhaustion was further evidenced by the fact that the expression of PD1, TIM3 and BTLA of exhausted T cells was increased by the inhibitor of miR28. On the other hand, miR-28 also regulated the PD1+ Foxp3+ and TIM3+ Foxp3+ exhaustive Treg cells in vitro. miR-28 regulating T cell exhaustion was also observed by its ability in reinstalling impaired secretion of cytokines IL-2 and TNF-α by exhausted T cells. This study is the first to discover the effect of miR-28 on T cell exhaustion, providing novel targets with potential use as therapeutic markers in cancer immunotherapy.